Successful Treatment of Acute Limb Ischemia Secondary to Iatrogenic Distal Embolization Using Catheter Directed Aspiration Thrombectomy - Farhat-Sabet, Ashley A.; Tolaymat, Besher; Voit, Antanina; Drucker, Charles B.; Santini-Dominguez, Rafael; Ucuzian, Areck A.; Toursavadkohi, Shahab A.; Nagarsheth, Khanjan H. (Frontiers in Surgery, 2020)
Objective: Acute limb ischemia (ALI) due to thromboembolism is a limb- and life-threatening condition regularly encountered by vascular surgeons. Iatrogenic distal embolization is occasionally seen as a complication of various endovascular procedures. We present a series of four patients who developed ALI due to arterial embolization during cardiovascular procedures that were successfully treated via catheter directed aspiration embolectomy. Methods: Retrospective review of demographics, risk factors, and procedural outcomes was completed for 4 patients who presented with ALI due to distal embolization following cardiovascular procedures. All patients were successfully treated with catheter directed aspiration embolectomy using the Penumbra Indigo System (Penumbra Inc., Alameda, California). All patients had high-quality angiography demonstrating successful embolectomy and end-procedure patency. Results: Three patients presented with Rutherford 2A and one with Rutherford 2B ALI secondary to intraoperative distal embolization. Three patients presented with ALI secondary to distal embolization during peripheral vascular interventions, and one following emergent intra-aortic balloon pump (IABP) placement for myocardial infarction. All emboli were located in the infra-inguinal vasculature. Median post-operative ABIs were 0.94 (n = 4). Median length of stay was 2 days. There were no mortalities and no need for adjunctive fasciotomy, amputation, or bypass for limb salvage. All patients improved clinically after intervention, and returned to their reported pre-hospitalization functional status. Conclusion: All procedures achieved technical success with catheter-directed aspiration thrombectomy with or without adjunctive lysis. Catheter-directed aspiration embolectomy with the Penumbra Indigo System for ALI following an iatrogenic embolic event is a safe, less-invasive treatment option. The use of this technology may reduce the need for traditional open thrombectomy or thrombolytic therapy to address ALI.